2020
DOI: 10.1038/s41467-020-16863-9
|View full text |Cite
|
Sign up to set email alerts
|

Topological framework for directional amplification in driven-dissipative cavity arrays

Abstract: Directional amplification, in which signals are selectively amplified depending on their propagation direction, has attracted much attention as key resource for applications, including quantum information processing. Recently, several, physically very different, directional amplifiers have been proposed and realized in the lab. In this work, we present a unifying framework based on topology to understand non-reciprocity and directional amplification in driven-dissipative cavity arrays. Specifically, we unveil … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 65 publications
4
109
0
Order By: Relevance
“…In particular, the quantity introduced below displays quantized plateaus that precisely match spectral winding numbers, making it possible to distinguish between one nontrivial point-gap topology from another. This is a true advance as compared with earlier interesting attempts where signal amplification was only used to probe NHSE under OBC 39,40 .…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…In particular, the quantity introduced below displays quantized plateaus that precisely match spectral winding numbers, making it possible to distinguish between one nontrivial point-gap topology from another. This is a true advance as compared with earlier interesting attempts where signal amplification was only used to probe NHSE under OBC 39,40 .…”
Section: Resultsmentioning
confidence: 88%
“…Such correspondence between spectral winding numbers and quantized response is arguably broader in scope than in the case of momentum-space topology, because spectral winding does not even require translational invariance. Our results are relevant to a number of current experimental platforms of non-Hermitian systems 30,31,33,39,[59][60][61] . In the context of classical electrical circuits, we have shown that a quantized response can be easily extracted from extremely experimentally accessible impedance measurements.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Devices that exploit the rotational inertia of the resonator, such as chiral structures [ 34 , 35 , 36 , 37 , 38 ] or gyroscopic spinners [ 29 ], are the most popular designs of directional amplifiers in periodic structures, where the longitudinal motion of the finite size mass elements is coupled to their rotation, following a spin. Directional amplification systems have also been implemented in other scientific fields, such as quantum information processing [ 39 ] in terms of controlling amplification and directionality of electromagnetic signals [ 40 ] as well as in photonic systems [ 41 , 42 ]. However, a different approach has been followed in those cases.…”
Section: Introductionmentioning
confidence: 99%
“…We shall, as customary in the context of quantum optics [4][5][6], define a coherent feedback loop as one where a set of output modes, interacting with a system at an input-output interface, may be manipulated through quantum CP maps and then fed back into a system as input modes at another interface. This approach is similar to that used in the established field of "cascaded quantum systems," where the output of one system is used as the input of another [7][8][9][10], and of the related "all-optical" feedback [11], the difference being that here the output is fed back into the system from whence it came.…”
Section: Introductionmentioning
confidence: 99%